How long should outpatient pulmonary rehabilitation be? A randomised controlled trial of 4 weeks versus 7 weeks - Sewell, L (BMJ Group, 2006)
BACKGROUND: The evidence of benefit for pulmonary rehabilitation (PR) programmes is established. However, the optimal duration of a PR programme is not known. A randomised controlled trial was undertaken in patients with chronic obstructive pulmonary disease (COPD) to assess whether a 4 week PR programme was equivalent to our conventional 7 week PR programme at equivalent time points of 7 weeks and 6 months. METHODS: One hundred patients (56 men) with stable COPD of mean (SD) age 70 (8) years and forced expiratory volume in 1 second (FEV(1)) 1.13 (0.50) litres were randomised to either a 7 week (n = 50) or 4 week (n = 50) supervised PR programme. Patients were assessed at baseline, at completion of the supervised PR programme, and 6 months later. Patients randomised to the 4 week group were also assessed at the 7 week time point. Outcome measures were the Incremental Shuttle Walk Test, Endurance Shuttle Walk Test (ESWT), Chronic Respiratory Questionnaire‐Self Reported, and the Breathing Problems Questionnaire. RESULTS: Forty one patients in each group completed the PR programme. Patients made significant within group improvements after supervised rehabilitation. There were no statistically significant differences between the groups for any other measure at the 7 week or 6 month time points, except that patients in the 4 week group attained higher ESWT times (mean difference 124 seconds (95% CI 17.00 to 232.16), p = 0.024) at the 7 week time point. CONCLUSIONS: A shortened 4 week supervised PR programme is equivalent to a 7 week supervised PR programme at the comparable time points of 7 weeks and 6 months.